Influence of Conditions of a Hot Metal Particle Thermal Contact with a Coal Dust Layer on Characteristics of GasPhase Ignition; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Paushkina K. K. Kristina Konstantinovna (2020, 2020)
Title screen